"With a Mighty Hand and an Outstretched Arm": On the Hand(s) of God in the Exodus Panel in the Dura-Europos Synagogue - Yuval-Hacham, Noa (Mabatim: Journal of Visual Culture, 2023)
The frescoes of the ancient synagogue at Dura-Europos (present-day Syria) pioneered the use of a visual image to embody the Divine presence and revelation in biblical contexts. The hand of God that represents the Divine presence appears in five of the synagogue’s murals, one of which – the Exodus panel – is the focus of this article. The discussion includes, on the one hand, broad scrutiny of the visual image of the hand of God that investigates its conceptual roots in Jewish thought and its iconographic sources; and on the other hand, focused consideration of the Exodus panel from iconographic and literary perspectives. The article also examines the image of the hand of God in visual depictions of the Exodus in Late Antiquity Jewish and Christian art.